Clip Migration in clipped intestinal non-perforating anastomosis (CINPA) - Holland-Cunz, Stefan; Chmelnik, Martin; Romero, Philipp; Klein, Birgit; Rumstadt, Bernhard (European journal of pediatric surgery, 2011)
Introduction: Our studies of clipped intestinal non-perforating anastomosis (CINPA) of the small bowel in a rat model have demonstrated that all clips migrated from the outside to the inside of the small bowel during the healing process. The aim of this study was to describe how the clips migrate. Material and Methods: In male Sprague Dawley rats small bowel anastomoses were performed with single, non-perforating metal clips. Bowel specimens were obtained from the anastomosed region for histological examination. Results: On the day of surgery all clips were situated in the serous membrane. On the first postoperative day, an intramural migration could be observed. By days 6, 8, and 10 no clip was found in the peritoneum. All egested clips were found either in the distal lumen of the bowel or in the solid feces. H&E staining of the anastomoses studies indicated that the bowel wall everts immediately after being cut and becomes more and more inverted during the first few days after being anastomosed. Conclusion: Our studies showed that the observed dynamic movement of the bowel wall determines the movement of clip migration from the serosal to the mucosal side of the small bowel. In pediatric surgery the observed clip migration would be an important precondition for employing clipped intestinal non-perforating anastomosis (CINPA) routinely. However, further studies are necessary before the technique can be applied in daily practice.
04. November 2010 (online)
Gesehen am 29.06.2022